Performance of UWB impulse radio with planar monopoles over on-human-body propagation channel for wireless body area networks - Zhang, Yue Ping (2009)
Ultrawideband (UWB) is a promising technology for wireless body area networks (WBANs). This paper studied the impacts of 3.1–10.6 GHz on-human-body UWB channel on the impulse radio WBAN system. A performance evaluation method is presented for the realistic UWB WBAN systems, which observes the waveform distortion along the signal path. The measurement and characterization of the 3.1–10.6 GHz on-human-body UWB channel are devised to generate the radiographs of path loss and delay spread for the first time. The performance of the UWB impulse radio WBAN transceiver in terms of bit error rate (BER) is evaluated based on the waveform distortion and on-human-body channel measurement, which shows the human body effect is more significant than the environment effect, especially when the propagation channel contains no line-of-sight path. Various candidate pulse shapes and modulation schemes forUWBWBAN are studied and their performances with the measured WBAN channel are evaluated and compared.